Late Lutetian Thermal Maximum—Crossing a Thermal Threshold in Earth's Climate System?. (12th January 2018) - Westerhold, T.; Röhl, U.; Donner, B.; Frederichs, T.; Kordesch, W. E. C.; Bohaty, S. M.; Hodell, D. A.; Laskar, J.; Zeebe, R. E.
Abstract: Recognizing and deciphering transient global warming events triggered by massive release of carbon into Earth's ocean‐atmosphere climate system in the past are important for understanding climate under elevated pCO2 conditions. Here we present new high‐resolution geochemical records including benthic foraminiferal stable isotope data with clear evidence of a short‐lived (30 kyr) warming event at 41.52 Ma. The event occurs in the late Lutetian within magnetochron C19r and is characterized by a ∼2°C warming of the deep ocean in the southern South Atlantic. The magnitudes of the carbon and oxygen isotope excursions of the Late Lutetian Thermal Maximum are comparable to the H2 event (53.6 Ma) suggesting a similar response of the climate system to carbon cycle perturbations even in an already relatively cooler climate several million years after the Early Eocene Climate Optimum. Coincidence of the event with exceptionally high insolation values in the Northern Hemisphere at 41.52 Ma might indicate that Earth's climate system has a thermal threshold. When this tipping point is crossed, rapid positive feedback mechanisms potentially trigger transient global warming. The orbital configuration in this case could have caused prolonged warm and dry season leading to a massive release of terrestrial carbon into the ocean‐atmosphere system initiating environmental change. Key Points: Eocene transient (30 kyr) warming event at 41.52 Ma The Late Lutetian Thermal Maximum (LLTM) occurs within magnetochron C19r and is characterized by a ∼2°C warming of the deep ocean in the southern South Atlantic LLTM coincidences with exceptionally high insolation pointing to a potential thermal threshold of Earth's climate system